ANALISIS PENGARUH ELEMEN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN PC TABLET APPLE IPAD (Studi Kasus Pada Konsumen Apple iPad di Kota Semarang) - Sudar, Dhany Pramana; Rahardjo, Susilo Toto (Faculty of Economics and Business Diponegoro University, 2014)
This research was motivated by the intense of Tablet PC competition in market with more popping up a variety of new brand, or old brand that continues to innovate with different offers and strategies to attract customers to be a market leader in Tablet PC market. This is impacting on the acquisition of brand value, brand share, potential gain index in the future, and the index of consumer satisfaction on iPad. This study aims to test the influence of brand equity elements which consist of Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty to the Purchasing Decision on iPad. After performing study of literature review and developing hypothesis, the data was collected by questionnaire method toward 100 persons iPad users in Semarang City, which obtained by using accidental sampling method. Then, we performed quantitative and qualitative analyses of the data will be tested. A quantitative analysis consist of Validity Test, Reliability Test, The Classic Assumption Test, Multiple Regression Analysis, Goodness of Fit Test that includes Analysis of Coefficient of Determination (R2), the F Test, and the t Test. Qualitative analysis is an interpretation of the data collected in this study, and result of data processing that have been implemented with a description and explanation. Then data were processed using SPSS (Statistical Package for Social Science) for Windows version 21 in a quantitative analysis that produced the regression equation as follows: Y = 0,141 X1 + 0,290 X2 + 0,300 X3 + 0,202 X4 Which is the Purchasing Decision variable (Y), Brand Awareness (X1), Brand Association (X2), Perceived Quality (X3), Brand Loyalty (X4). Hypotheses testing using the F Test can be known that fourth independent variable get a well-deserved to test Purchase Decision as the dependent variable. Then through the t Test showed that the four independent variables that studied have positive and proved significantly to influence the Purchase Decision. Meanwhile, the acquisition rate of 0,715 on the Adjusted R Square indicated that 71,5% of Purchase Decisions variation can be explained by the variation of the four independent variables in the regression equation. Whereas 28,5% as the rest of it was explained by other variables outside of the four variables used in this study.